2018
DOI: 10.1111/anec.12533
|View full text |Cite
|
Sign up to set email alerts
|

Baseline fragmented QRS increases the risk of major arrhythmic events in hypertrophic cardiomyopathy: Systematic review and meta‐analysis

Abstract: Baseline fQRS increased major arrhythmic events up to sevenfold. Our study suggests that fQRS could be an important tool for risk assessment in patients with HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…And the peri‐infarct area in STEMI patient serves as a substrate for arrhythmia . Previous meta‐analyses had demonstrated that fQRS increased arrhythmic events in patients with hypertrophic cardiomyopathy and Brugada syndrome . For STEMI patients, our meta‐analysis argued that fQRS on ECG also increases the risk of VTAs 2.81‐fold.…”
Section: Discussionmentioning
confidence: 65%
“…And the peri‐infarct area in STEMI patient serves as a substrate for arrhythmia . Previous meta‐analyses had demonstrated that fQRS increased arrhythmic events in patients with hypertrophic cardiomyopathy and Brugada syndrome . For STEMI patients, our meta‐analysis argued that fQRS on ECG also increases the risk of VTAs 2.81‐fold.…”
Section: Discussionmentioning
confidence: 65%
“…Fragmented QRS (fQRS), which reflects myocardial scarring, has been found to be associated with poor prognostic outcome in several cardiac conditions, including coronary artery disease (Xu et al, 2015), non-ischemic cardiomyopathy (Das et al, 2010), Brugada syndrome (Rattanawong et al, 2017), chronic total occlusion (Bonakdar et al, 2016), and hypertrophic cardiomyopathy (Rattanawong et al, 2018). Recent studies have demonstrated poor prognostic outcome in HFrEF patients whose baseline ECG was positive for fQRS.…”
Section: Introductionmentioning
confidence: 99%
“…meta-analysis showed that baseline fQRS significantly increased the risk of major arrhythmic events in HCM patients. 16 An observational study showed that a myocardial scar visualized by CMR with LGE predicted major adverse events in HCM patients, 10 but the cost and availability of CMR prevents repetitive testing during long-term follow-up. Thus, more convenient and safer clinical measures to assess cardiac event risks in HCM patients are needed.…”
Section: Discussionmentioning
confidence: 99%
“…10 An association between baseline fQRS and the occurrence of VAEs has also been reported in HCM patients, [11][12][13][14][15] and a recent meta-analysis showed a significant increase in arrhythmic events in HCM patients with baseline fQRS. 16 However, in some HCM patients without baseline fQRS, fQRS newly appears during follow-up, and little is known about the significance of this newly appeared fQRS. In 1 case report, an HCM patient with new appearance of fQRS was reported to have VAEs 7 years after the baseline ECG, 17 but an association between cardiac events and the disc summation method.…”
Section: Ecg Recording and Definition Of Fqrsmentioning
confidence: 99%